GERIAYUTRICS – AYURVEDIC PERSPECTIVE OF SENESCENCE AND REJUVENESCENCE - N. Dornala, *Sathya; SN Dornala, Snehalatha (AYUSHDHARA, 2016)
Ayurveda itself is seen to have been evolved to ease human beings from Jara. Inclusion of Jara chikitsa (Geriayutrics) as one among the Ashtanga Ayurveda during those good olden days implies the foresight of Acharyas on its importance. World Health Organisation declared the calendar year 1999 as the International Year of Older People (IYOP), since then the problems of aging people got the worldwide focus and health wise momentum. Now at this time, the whole world is showing renewed interest in the aging process and aged people. In first 50 yrs of 21st century old age dependency ratio is expected to double in more developed region and triple in less developed region, thus the aged people are going to be a big problem for the society.It is the best time to explore the possibilities from Ayurveda, which can raise the hope of the silver population and improve their lifespan. The cognate of the Greek “Geras” is the Sanskrit “Jara” both of which means old age. According to Ayurveda, the Jara (aging) is a natural phenomenon like hunger, thirst and sleep. Sushruta mentioned a group of naturally occurring diseases named Svabhavabala roga, which includes Kshut (hunger), Pipasa (thirst), Nidra (sleep), Jara (old age) and Mrityu (death). The term ‘Geriayutrics’ is introduced by the authors to emphasize that Ayurveda is the science recognised importance of Jara Chikitsa as separate clinical speciality. This review focuses on the understanding of Ayurvedic biology of aging with respect to physiological components such as Dosha, Dhatu, Mala, Srotas, Indriyas, Ojas, Manas and so on and their correction through the application of Rasayana (rejuvenescence).